2003
DOI: 10.1128/mcb.23.8.2953-2968.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 303 Is a Prerequisite for the Stress-Inducible SUMO Modification of Heat Shock Factor 1

Abstract: The heat shock response, which is accompanied by a rapid and robust upregulation of heat shock proteins (Hsps), is a highly conserved protection mechanism against protein-damaging stress. Hsp induction is mainly regulated at transcriptional level by stress-inducible heat shock factor 1 (HSF1). Upon activation, HSF1 trimerizes, binds to DNA, concentrates in the nuclear stress granules, and undergoes a marked multisite phosphorylation, which correlates with its transcriptional activity. In this study, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
258
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(273 citation statements)
references
References 67 publications
12
258
1
2
Order By: Relevance
“…It seems, therefore, that Ha-ras val12 expression does not have a significant effect on Hsf1 phosphorylation. The fact that Ras properly regulated HSF1 S303A rules out the possibility that Ras affect SUMO-1 modification, because Ser303 phosphorylation is a prerequisite for this modification (Hietakangas et al, 2003). In order to evaluate a possible effect of Ras on Hsf1 redox state, we measured the in vivo redox state of Hsf1 upon cotransfection with Ha-ras val12 .…”
Section: Resultsmentioning
confidence: 99%
“…It seems, therefore, that Ha-ras val12 expression does not have a significant effect on Hsf1 phosphorylation. The fact that Ras properly regulated HSF1 S303A rules out the possibility that Ras affect SUMO-1 modification, because Ser303 phosphorylation is a prerequisite for this modification (Hietakangas et al, 2003). In order to evaluate a possible effect of Ras on Hsf1 redox state, we measured the in vivo redox state of Hsf1 upon cotransfection with Ha-ras val12 .…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation could also account for the coexistence of the nonsumoylated and sumoylated forms of RGSZ1 and GAIP. Indeed, proteins like heat stress factor 1 must be phosphorylated to undergo efficient sumoylation (Hietakangas et al, 2003), although the contrary has been observed for the transcription factor c-Jun, the sumoylation of which is downregulated after phosphorylation (Müller et al, 2000). As sumoylation can be regulated by phosphorylation, it is possible that phosphorylation of critical residues on RGSZ1 impairs SUMO conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…MEFs derived from an Hsf1 Ϫ/Ϫ or Hsf1 ϩ/ϩ mouse (19) were maintained as in ref. 37. For heat shock treatments, the plates were immersed in a water bath set to the indicated temperature (Ϯ0.1°C).…”
Section: Methodsmentioning
confidence: 99%